Reinforcement mechanism of rockbolt system for underground excavation - Nie, Wen (2019)
A rockbolt is a reinforcing element installed untensioned or tensioned into the ground to restrict the deformation of the surrounding rock mass in rock engineering. The rockbolt is usually a solid bar or tube element which is installed within the boreholes drilled into the rock. To improve the rockbolt design in complex rock conditions, it is necessary to have a good understanding of the reinforcement mechanism of the rockbolts. In this thesis, the reinforcement mechanism of a rockbolt system under excavation conditions is studied using the two-dimensional discontinuous deformation analysis (2D-DDA) method and other numerical tools. The load transfer capacity of a rockbolt element is controlled by the components of bonds at the rock and rockbolt, such as the rock mass, the mortar and the profile configuration of the rockbolt. 2D-DDA method is used to investigate the pullout performance of a continuously mechanically coupled (CMC) rockbolt element. The flat joint contact model is introduced into the 2D-DDA code to simulate the force versus displacement behaviour of an artificial joint. Parametric studies show that the confining pressure plays an important role in the bond-slip modeling. The obtained key parameters of the trilinear bond-slip model can be used to simulate the bond behaviour between the rockbolt and rock under similar conditions. A rockbolt model is developed and integrated into the 2D-DDA code based on the load transfer theory. Three mechanical behaviours are considered in the model, i.e., the bond, the axial tension and the shear at joint. The proposed rockbolt model could be used to simulate four major failure modes of rockbolt, such as the de-bonding along the interface, tensile failure, faceplate failure and shear failure. The numerical results show that the numerical models have reasonable agreements with the experiments results. The parameter studies show that the load transfer and load capacity should be reconsidered when the ground conditions are changed. The rock/rockbolt interactions are examined by simulating the pullout test in rock mass with systematic joint sets. The effects of the rock properties, joint orientations, rockbolt lengths and in-plane spacing are studied. The reinforcement rock unit (RRU) induced by single rockbolt is normally in a cone shape and restrained by the orientation of the discontinuities. The RRU induced by grouped rockbolts is heavily influenced by the joint orientations and the rockbolt spacing. Further applications of the RRUs on the estimation of the artificial pressure arch in the roof are illustrated. The rockbolt to stabilize roof wedges in underground opening is studied using the joint relaxation method to consider the rock wedge in deformable rock conditions. Parametric studies are carried out to investigate the key parameters that influence the effects of rockbolts when they are used to stabilize the rock wedge. The results show that 2D-DDA could be used to find the critical horizontal pressure to sustain the rock wedges. A cross section in storage gallery in Jurong Rock Caverns (JRC), Singapore, is conducted to show the application of the 2D-DDA models for rockbolt design to support roof wedges. The stress versus vertical displacement curves showed clearly the effect of rockbolt on sustaining the movement of rock wedge. The way to create characteristic diagram could be used by the site engineers to evaluate the rockbolting design to sustain the possible roof wedges. A support design method for horseshoe-shaped rock caverns is proposed with considerations of the progressive damage of the rock mass using the 2D finite element method (FEM) and the artificial neural network (ANN). The performances of the rock cavern during excavation are investigated based on the convergence-confinement method (CCM). The ANN models are built using the numerical results to find the complex relationships among the rock mass condition, the sequential excavation parameters and the cavern performances. An evaluation chart is proposed by integrating the ANN models into the EXCEL software. The proposed evaluation chart provides an effective method to evaluate the support safety, the functions of the patterned rockbolt and the optimization of subdivisions of the excavation cross section. More advanced function is still required to present the relationship between the parameters of sequential excavation method (SEM) and the cavern performance.